Velocity associated characteristics of force production in college weight lifters - Kanehisa, H.; Fukunaga, T. (British Journal of Sports Medicine, 1999)
OBJECTIVE: To determine velocity specific isokinetic forces and cross sectional areas of reciprocal muscle groups in Olympic weight lifters. METHODS: The cross sectional area of the flexor or extensor muscles of the elbow or knee joint was determined by a B-mode ultrasonic apparatus in 34 college weight lifters and 31 untrained male subjects matched for age. Maximum voluntary force produced in the flexion and extension of the elbow and knee joints was measured on an isokinetic dynamometer at 60, 180, and 300 degrees/s. RESULTS: The average cross sectional area was 31-65% higher, and the force was 19-62% higher in weight lifters than in the untrained subjects. The ratio of force to cross sectional area was the same in both groups. The weight lifters showed a lower velocity associated decline in force than untrained subjects in the elbow and knee flexors but not in the extensors. CONCLUSIONS: These results indicate that for muscle contractions with velocities between 60 degrees/s and 300 degrees/s the difference in isokinetic force between weight lifters and untrained subjects can be primarily attributed to the difference in the muscle cross sectional area. However, the lower velocity associated decline in force implies that weight lifters may have a higher force per cross sectional area than untrained subjects at velocities above 300 degrees/s.